The Seventh Grade Students’ Generalization Strategies of Patterns - Mu'jizatin Fadiana; Siti M Amin; Agung Lukito (Journal of Education and Learning (EduLearn), 2018)
This article describes a generalization strategy on pictorial visual patterns. This explorative descriptive study involves 60 students of 7 Grade Student of private junior high school in Tuban East Java Indonesia. Data obtained through the pattern generalization task. The type of pattern used in this research is pictorial sequences with two non-consecutive terms. Selection of a pictorial sequences with two non-consecutive pattern to focus students' attention on visual stimuli. Based on the students answers of pattern generalization task, there are 33 students who answered correctly and 27 students answered wrong. From the correct answer, there are six different general formula representations. The visualization strategy used by the students begins by splitting the image into smaller elements. The way students break down into smaller elements is also diverse. Students divide the image in the form of V (2 matchsticks), U shape (3 matchsticks), square shape (4 matchsticks) and lastly divide in a unit additive consisting of 7 matchsticks.